2003
DOI: 10.1152/ajpgi.00165.2003
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a functional apical sodium hydrogen exchanger in isolated rat gastric glands

Abstract: Previous studies have shown that gastric glands express at least sodium-hydrogen exchanger (NHE) isoforms 1-4. Our aim was to study NHE-3 localization in rat parietal cells and to investigate the functional activity of an apical membrane NHE-3 isoform in parietal cells of rats. Western blot analysis and immunohistochemistry showed expression of NHE-3 in rat stomach colocalizing the protein in parietal cells together with the β-subunit of the H+-K+-ATPase. Functional studies in luminally perfused gastric glands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…For example, the role of NHE isoforms 1-4 in pH balance was investigated on parietal cells of stomach tissue (25). By preferentially inhibiting NHE-3 activity using low-dose EIPA, researchers demonstrated that Na ϩ /H ϩ exchange isoforms offered an alternative pathway for H ϩ ion removal from the apical surface of the parietal glands (25).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the role of NHE isoforms 1-4 in pH balance was investigated on parietal cells of stomach tissue (25). By preferentially inhibiting NHE-3 activity using low-dose EIPA, researchers demonstrated that Na ϩ /H ϩ exchange isoforms offered an alternative pathway for H ϩ ion removal from the apical surface of the parietal glands (25).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the forward mode of heterologously expressed NHE2 Na/H exchange is fully inhibited when extracellular pH is below pH 6 (41). Elegant experiments have shown that the apical NHE3 present in rat parietal cells inactivates when acid secretion is ongoing (17) but that the basolateral NHE in guinea pig surface cells is active at luminal pH 1.5-5 (18). Although NHE2 activation by either damage or TFF remains unproven, in this scenario, it could produce an advantageous raising of surface pH to promote epithelial repair with cells exposed to a less stressful pH environment (as long as the resultant cellular acid load could be handled by buffers or basolateral transporters).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue was then transferred to the stage of a dissecting microscope and sliced into 0.5-cm square sections. Individual glands were isolated using a hand dissection technique as described previously (8,13) at a temperature of about 10°C. After isolation, the glands were transferred to coverslips precoated with adhesive Cell-Tak (BD Cell-Tak Cell and Tissue Adhesion, BD Biosciences) and mounted in a thermostatically controlled chamber maintained at 37°C on an inverted microscope (Zeiss Axiovert 200) equipped with an video-imaging system for the duration of the experiment.…”
Section: Isolation Of Gastric Glands and Digital Imaging For Intracelmentioning
confidence: 99%
“…Human stomach samples were washed several times with PBS and fixed by immersion with paraformaldehydelysine-periodate fixative (16) overnight at 4°C. Stomachs were washed three times with PBS, and thin sections were cut at a thickness of 5 m after cryoprotection with 2.3 M sucrose in PBS for at least 12 h. Immunostaining was carried out as described previously (13). Sections were incubated with 1% SDS for 5 min, washed three times with PBS, and incubated with PBS containing 1% BSA for 15 min before incubation with the primary antibody.…”
Section: Isolation Of Gastric Glands and Digital Imaging For Intracelmentioning
confidence: 99%